2008
DOI: 10.1108/07419050810877535
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Library Orientations on Student Usage of the Library

Abstract: PurposeThis study examines the effect of information literacy orientations on usage statistics in an academic library. The aim of the study is to show that library orientations increase student usage of the library.Design/methodology/approachThe paper analyzes student usage statistics at Cochise College Library.FindingsAnalysis of survey data collected at Cochise College Library revealed a significant increase in usage of the library by students who received an orientation.Originality/valueThis paper describes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…Relating class instruction to ICT literacy skills, Waldman (2003) reported that incoming students of Baruch College, City University of New York are very familiar and use the Internet and library's e-resources with ease and age or gender had no significant effect on them because they had participated in information literacy initiative given by library faculty. Walsh (2008) revealed a significant increase in library use by students who received orientation at the University of Arizona, USA. Similarly, Gilbert (2009) opined that students who had multiple library instruction session during the first semester reported higher levels of confidence and greater use of library resources than students who had single instruction session.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Relating class instruction to ICT literacy skills, Waldman (2003) reported that incoming students of Baruch College, City University of New York are very familiar and use the Internet and library's e-resources with ease and age or gender had no significant effect on them because they had participated in information literacy initiative given by library faculty. Walsh (2008) revealed a significant increase in library use by students who received orientation at the University of Arizona, USA. Similarly, Gilbert (2009) opined that students who had multiple library instruction session during the first semester reported higher levels of confidence and greater use of library resources than students who had single instruction session.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An innovative and creative multimedia‐based library orientation programme in the college will improve the knowledge of the student. The recent studies have also attested the same findings (Walsh, 2008; Madhusudhan and Reetu, 2008; Lilili, 2006; Dent, 2004; Rudasill, 1999), which can potentially change the way in which physical orientation is handled and make information accessible from anywhere. This, of course, is an achievable goal.…”
Section: Discussionmentioning
confidence: 65%
“…According to Walsh (2008) and Omeluzor, Bamidele, Onuoha and Alarape (2013), library information literacy programmes are usually organised by the university libraries and in most cases, cover lecture or tutorial, seminar, workshop, one-on-one discussion, online courses, computer aided instruction, user education, library tour and briefing by librarians. Specifically, library orientation is only meant to educate newly admitted students of the University.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, many studies have been carried out to examine the impact of information literacy programmes on academic performance of students. According to Walsh (2008), library orientation is the most commonly used techniques of increasing students familiarity with the library and its resources; hence, a survey carried out by him within the Ventura College indicated that there was a significant increase in students patronage statistics of the Ventura College Libraries as a result of increased library orientations to promote usage of library's resources and services. Also, another study undertaken in Dublin City University library discovered that the institution's revamped library orientation programme was a significant contributing factor in the increased popularity and renewed interest exhibited by patrons.…”
Section: Literature Reviewmentioning
confidence: 99%